Anti-reduction pulse energy storage ceramic dielectric material and preparation method and application thereof
By using a combination of strontium calcium zirconate titanate and specific dopants in the ceramic dielectric material of MLCC with base metal electrodes and sintering in a reducing atmosphere, the problems of low dielectric constant, high dielectric loss and wide temperature coefficient are solved, realizing a high-reliability and low-cost reducing pulse energy storage ceramic dielectric material suitable for MLCC in electronic communication systems.
Patent Information
- Application Number
- CN202511141325.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-14
- Publication Date
- 2025-11-18
AI Technical Summary
Existing ceramic dielectric materials for MLCCs with base metal electrodes are easily reduced in a reducing atmosphere, resulting in low dielectric constant, high dielectric loss, low insulation resistance, wide capacitance temperature coefficient, and low reliability, making it difficult to meet the requirements of high reliability and low cost.
Using calcium strontium zirconate titanate as the main material, supplemented by oxides or carbonates of elements such as Mn, Cr, Co, and Fe, oxides or carbonates of elements such as Ba, Mg, Zr, Ca, Sr, and Ti, oxides of elements such as Ho, Y, Er, Dy, and Sm, and oxides of Mo and V as dopants, a reduction-resistant pulse energy storage ceramic dielectric material is formed by sintering in a reducing atmosphere, thereby improving the dielectric constant, reducing dielectric loss, and improving temperature stability.
It achieves high dielectric constant (≥100), low dielectric loss (≤0.02%), narrow capacitance temperature coefficient (-750±250ppm/℃) and high reliability, and is suitable for capacitors composed of base metal electrodes. It has the advantages of environmental friendliness and low cost.
Smart Images

Figure CN120965319A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of ceramic dielectric materials, and particularly relates to a reduction-resistant pulse energy storage ceramic dielectric material and a preparation method and application thereof. BACKGROUND
[0002] Multi-layer Ceramic Capacitors (MLCC) are layered devices composed of ceramic dielectric and metal electrodes. With the rapid development of 5G / 6G electronic communication systems, there is an increasing demand for low-cost, low-dielectric loss, high-dielectric, high-reliability, narrow-capacitance-temperature-coefficient, and miniaturized electronic components. Meanwhile, the development of large-capacitance and multi-layer MLCC also leads to an increase in the use of metal electrodes and costs. The use of base metal (such as copper and nickel) electrode materials instead of traditional silver-palladium electrodes can significantly reduce costs, but base metal electrode materials are easily oxidized and must be sintered in a reducing atmosphere. Traditional ceramic dielectric materials are easily reduced to become semiconductors when sintered in a neutral or reducing oxygen partial pressure, which leads to the degradation of the reliability of MLCC.
[0003] For ceramic dielectric materials for MLCC with base metal electrodes, not only the problem of resistance to reduction needs to be solved, but also certain electrical performance requirements need to be met. The existing formula technology has the disadvantages of low dielectric constant, high dielectric loss, low insulation resistance, wide capacitance temperature coefficient, or low reliability, and is difficult to meet the needs of pulse energy storage MLCC with base metal electrodes.
[0004] Generally, the higher the dielectric constant, the greater the loss, and the dielectric loss is the ratio of the loss coefficient to the dielectric constant of the material. There are many documents and patents in the existing reduction-resistant ceramic dielectric material technology that meet the conditions of dielectric constant ≥ 100 or capacitance temperature coefficient narrower than (-1000-1000) ppm / ℃, but there is no reduction-resistant pulse energy storage ceramic dielectric material that meets both conditions and has a room temperature dielectric loss lower than 0.02%. SUMMARY
[0005] Therefore, the purpose of the present application is to provide a reduction-resistant pulse energy storage ceramic dielectric material and a preparation method and application thereof. The reduction-resistant pulse energy storage ceramic dielectric material provided by the present application has a high dielectric constant (≥ 100), a low room temperature dielectric loss (≤ 0.02%), a narrow capacitance temperature coefficient (-750 ± 250 ppm / ℃), and high reliability, and can form a capacitor with a base metal electrode.
[0006] To achieve the above purpose, the present application provides the following technical solutions:
[0007] The application provides an anti-reduction type pulse energy storage ceramic dielectric material, and preparation raw materials include calcium zirconium titanate, auxiliary materials and sintering aids.
[0008] The chemical formula of the calcium zirconium titanate is [(Ca x Sr 1-x )O] m [(Ti y Zr 1-y )O2], 0.43<=x<=1, 0.45<=y<=0.53, 0.85<=m<=1.30.
[0009] The auxiliary materials include R1, R2, R3 and R4.
[0010] The R1 includes oxides or carbonates of at least one element in Mn, Cr, Co and Fe.
[0011] The R2 includes oxides or carbonates of at least one element in Ba, Mg, Zr, Ca, Sr and Ti.
[0012] The R3 includes oxides of at least one element in Ho, Y, Er, Dy and Sm.
[0013] The R4 includes oxides of at least one element in Mo and V.
[0014] Preferably, the mass ratio of the R1 to the calcium zirconium titanate is 0.01-0.2:100; the mass ratio of the R2 to the calcium zirconium titanate is 0.2-1.2:100; the mass ratio of the R3 to the calcium zirconium titanate is 0.3-1.3:100; and the mass ratio of the R4 to the calcium zirconium titanate is 0.01-0.06:100.
[0015] Preferably, the sintering aid includes SiO2 and / or B2O3; and the mass ratio of the sintering aid to the calcium zirconium titanate is 0.1-0.4:100.
[0016] Preferably, the preparation method of the calcium zirconium titanate includes the following steps: mixing raw materials corresponding to each element in the calcium zirconium titanate according to stoichiometric ratio, and calcining to obtain the calcium zirconium titanate.
[0017] Preferably, the calcining temperature is 1100-1200 DEG C, and the holding time is 1-3h.
[0018] The application further provides a preparation method of the anti-reduction type pulse energy storage ceramic dielectric material.
[0019] Mixing the calcium zirconium titanate, the auxiliary materials and the sintering aid, and sintering in a reducing atmosphere to obtain the anti-reduction type pulse energy storage ceramic dielectric material.
[0020] The auxiliary material comprises R1, R2, R3 and R4;
[0021] The R1 comprises an oxide or carbonate of at least one element of Mn, Cr, Co and Fe;
[0022] The R2 comprises an oxide or carbonate of at least one element of Ba, Mg, Zr, Ca, Sr and Ti;
[0023] The R3 comprises an oxide of at least one element of Ho, Y, Er, Dy and Sm;
[0024] The R4 comprises an oxide of at least one element of Mo and V.
[0025] Preferably, the calcium strontium zirconate titanate and the auxiliary material are mixed or the calcium strontium zirconate titanate, the auxiliary material and the sintering aid are mixed in a wet ball milling manner; the wet ball milling speed is 250-350 rpm, and the time is 4-8 h.
[0026] Preferably, the sintering comprises: after the first sintering, cooling to perform the second sintering; the temperature of the first sintering is 1250-1280℃, and the holding time is 2-3 h; the temperature of the second sintering is 990-1010℃, and the holding time is 3-5 h.
[0027] The application further provides an application of the anti-reduction type pulse energy storage ceramic dielectric material in a capacitor.
[0028] The application further provides a capacitor comprising a ceramic substrate and a metal electrode covering the surface of the ceramic substrate, wherein the ceramic substrate is the anti-reduction type pulse energy storage ceramic dielectric material or the anti-reduction type pulse energy storage ceramic dielectric material prepared by the preparation method.
[0029] The application provides an anti-reduction type pulse energy storage ceramic dielectric material, and preparation raw materials comprise calcium strontium zirconate titanate, an auxiliary material and a sintering aid.
[0030] The chemical formula of the calcium strontium zirconate titanate is [(Ca x Sr 1-x )O] m [(Ti y Zr 1-y )O2], 0.43≤x≤1, 0.45≤y≤0.53, 0.85≤m≤1.30;
[0031] The auxiliary material comprises R1, R2, R3 and R4;
[0032] The R1 includes an oxide or carbonate of at least one element among Mn, Cr, Co and Fe;
[0033] The R2 includes an oxide or carbonate of at least one element among Ba, Mg, Zr, Ca, Sr and Ti;
[0034] The R3 includes an oxide of at least one element among Ho, Y, Er, Dy and Sm;
[0035] The R4 includes an oxide of at least one element among Mo and V.
[0036] The anti-reduction type pulse energy storage ceramic dielectric material provided by the application has excellent anti-reduction performance, the R1 type and R4 type doping ions doped in the ceramic dielectric material play the role of acceptor in the sintering process of the ceramic dielectric material, the oxygen vacancy concentration caused by the doping ions is greater than the oxygen vacancy concentration caused by oxygen volatilization, the occurrence of electronic conduction is inhibited to a certain extent, the semi-conductivity of the perovskite crystal structure ceramic material is hindered, the anti-reduction performance of the main material is improved, the tetravalent ions in the B position are not easy to be reduced to trivalent ions in a high-temperature reducing atmosphere, the anti-reduction type pulse energy storage ceramic dielectric material can also maintain high insulation resistance when sintered in a reducing atmosphere, the insulation resistance of the ceramic dielectric material at room temperature and high temperature is greatly improved, the high reliability of the ceramic dielectric material is ensured, and the service life of the MLCC is improved. The R2 type doping ions can promote the mass transfer process of the anti-reduction type pulse energy storage ceramic dielectric material, improve the ceramic density, and thus reduce the room temperature dielectric loss and improve the dielectric constant. The R3 type doping ions play the role of amphoteric ions, successfully improve the temperature stability of the ceramic dielectric material, and make the anti-reduction type pulse energy storage ceramic dielectric material have a narrow capacity temperature coefficient (-750±250 ppm / ℃) in the range of -55 to 125℃, wherein the optimal group capacity temperature coefficient (TC) meets the temperature stability requirements of UH type dielectric material, and has extremely high temperature stability. The content of titanium in the calcium strontium zirconate titanate main material can also reduce the room temperature dielectric loss and improve the dielectric constant. Therefore, the anti-reduction type pulse energy storage ceramic dielectric material provided by the application has low dielectric loss, the dielectric loss at room temperature is not more than 0.02%; has extremely high insulation resistivity ≥10 13 Ω·cm at 25℃ and 125℃, has high reliability; has high dielectric constant, the dielectric constant at room temperature is 100 or higher; has narrow capacity temperature coefficient and high temperature stability.
[0037] The anti-reduction type pulse energy storage ceramic dielectric material provided by the application has simple formula and low cost, does not contain lead, is environment-friendly, has good application prospect, and has simple and controllable preparation method and is easy to be mass produced industrially. BRIEF DESCRIPTION OF DRAWINGS
[0038] Figure 1SEM image of the main material calcium strontium zirconate titanate prepared in Example 13;
[0039] Figure 2 XRD image of the main material calcium strontium zirconate titanate prepared in Example 13;
[0040] Figure 3 Cross-section SEM image of the ceramic wafer prepared in Example 13;
[0041] Figure 4 Surface SEM image of the ceramic wafer prepared in Example 13. DETAILED DESCRIPTION
[0042] The present application provides an anti-reduction pulse energy storage ceramic dielectric material, and the preparation raw materials include calcium strontium zirconate titanate, auxiliary materials and sintering aids.
[0043] The chemical formula of the calcium strontium zirconate titanate is [(Ca x Sr 1-x )O] m [(Ti y Zr 1-y )O2], 0.43≤x≤1, 0.45≤y≤0.53, 0.85≤m≤1.30.
[0044] The auxiliary materials include R1, R2, R3 and R4.
[0045] The R1 includes oxides or carbonates of at least one element of Mn, Cr, Co and Fe.
[0046] The R2 includes oxides or carbonates of at least one element of Ba, Mg, Zr, Ca, Sr and Ti.
[0047] The R3 includes oxides of at least one element of Ho, Y, Er, Dy and Sm.
[0048] The R4 includes oxides of at least one element of Mo and V.
[0049] Unless otherwise specified, the present application does not have special requirements for the source of the raw materials used, and commercially available goods known to those skilled in the art can be used.
[0050] As an embodiment, 0.5≤x≤0.85, 0.46≤y≤0.5, 1.0≤m≤1.2.
[0051] As an embodiment, the preparation method of the calcium strontium zirconate titanate includes the following steps: mixing the raw materials corresponding to each element in the calcium strontium zirconate titanate according to the stoichiometric ratio, and calcining to obtain the calcium strontium zirconate titanate.
[0052] As an embodiment, the raw material corresponding to each element in the strontium calcium zirconate titanate is a powder; the particle size of the powder is 50-200 nm, and in a specific embodiment, 50-180 nm; the purity of the raw material corresponding to each element in the strontium calcium zirconate titanate is 99.5-99.9%, and in a specific embodiment, 99.9%; the raw material corresponding to the zirconium element in the strontium calcium zirconate titanate is ZrO2, the raw material corresponding to the titanium element is TiO2, the raw material corresponding to the strontium element is SrCO3, and the raw material corresponding to the calcium element is CaCO3; the mixing is wet ball milling; the rotation speed of the wet ball milling is 250-350 rpm, and in a specific embodiment, 300 rpm; the time is 5-8 h, and in a specific embodiment, 6 h; the ball milling medium used in the wet ball milling is a zirconia ball; the diameter of the zirconia ball is 3-20 mm; in a specific embodiment, the zirconia ball includes graded zirconia balls with a diameter of 3 mm, a diameter of 10 mm, and a diameter of 15 mm, wherein the mass ratio of the zirconia ball with a diameter of 3 mm, the zirconia ball with a diameter of 10 mm, and the zirconia ball with a diameter of 15 mm is 4:2:1; the ball-to-material ratio during the wet ball milling is 10-50:1, and in a specific embodiment, 30:1; the solvent used in the wet ball milling is water, and in a specific embodiment, deionized water; the ratio of the total mass of the raw material corresponding to each element in the strontium calcium zirconate titanate to the weight of the solvent used in the wet ball milling during the wet ball milling is 1:2-3, and in a specific embodiment, 1:2.5; after the wet ball milling, the mixture liquid after the wet ball milling is further dried; the temperature of the drying is 120-150°C, and in a specific embodiment, 125°C; the time is 10-12 h, and in a specific embodiment, 11 h; the particle size of the powder obtained after the wet ball milling is 50-100 nm, and in a specific embodiment, 50-80 nm.
[0053] As an embodiment, the calcination is performed in an air atmosphere; the temperature of the calcination is 1100-1200°C, and in a specific embodiment, 1160°C; the holding time is 1-3 h, and in a specific embodiment, 2 h.
[0054] As an embodiment, after the calcination, the method further comprises: ball-milling dispersing the calcined product; the ball-milling dispersing time is 4-8h, and in particular embodiments, 6h; the ball-milling dispersing is wet ball-milling; the wet ball-milling speed is 200-300rpm, and in particular embodiments, 250rpm; the wet ball-milling uses zirconia balls as the ball-milling medium; the zirconia balls have a diameter of 3-10mm; in particular embodiments, the zirconia balls include graded zirconia balls with a diameter of 3mm and a diameter of 5mm, wherein the mass ratio of the zirconia balls with a diameter of 3mm to the zirconia balls with a diameter of 5mm is 1:2; the ball-to-material ratio in the wet ball-milling process is 5-10:1, and in particular embodiments, 7:1; the wet ball-milling uses water as the solvent, and in particular embodiments, deionized water; the mass ratio of the calcined product to the solvent used in the wet ball-milling is 1:2-3, and in particular embodiments, 1:2.5; the particle size of the powder obtained after the wet ball-milling is 150-250nm, and in particular embodiments, 200-250nm; after the wet ball-milling, the method further comprises: drying the mixture liquid after the wet ball-milling; the drying temperature is 120-150℃, and in particular embodiments, 125℃, and the drying time is 10-12h, and in particular embodiments, 11h.
[0055] As an embodiment, R1 is an oxide or carbonate of Mn; R2 is an oxide or carbonate of at least one element selected from Mg, Ba and Ca; R3 is an oxide of at least one element selected from Ho, Y and Dy; and R4 is an oxide of V.
[0056] As an embodiment, the mass ratio of R1 to calcium strontium zirconate is 0.01-0.2:100, and in particular embodiments, 0.08:100; the mass ratio of R2 to calcium strontium zirconate is 0.2-1.2:100, and in particular embodiments, 1.03:100; the mass ratio of R3 to calcium strontium zirconate is 0.3-1.3:100, and in particular embodiments, 1.24:100; and the mass ratio of R4 to calcium strontium zirconate is 0.01-0.06:100, and in particular embodiments, 0.01:100.
[0057] As an embodiment, the sintering aid comprises SiO2 and / or B2O3, and in particular embodiments, SiO2; and the mass ratio of the sintering aid to calcium strontium zirconate is 0.1-0.4:100, and in particular embodiments, 0.3:100. The present application uses Si element as a sintering aid to reduce and widen the sintering temperature.
[0058] As one implementation, the dielectric loss of the anti-reduction pulse energy storage ceramic dielectric material is ≤0.02% at room temperature, specifically 0.009~0.018% in this embodiment, and the insulation resistivity is ≥10 at both 25℃ and 125℃. 13 In specific embodiments, the insulation resistivity at 25°C is (49.48~66.17)×10 Ω·cm. 13 The insulation resistivity at 125℃ is (1.15~1.71)×10 Ω·cm. 13 The dielectric constant is ≥100 Ω·cm at room temperature, specifically 100~115 in the embodiment; within the temperature range of -55~125℃, the anti-reduction pulse energy storage ceramic dielectric material meets the temperature stability requirements of UK type (-750±250ppm / ℃) dielectric materials specified in the national standard (GB / T5596-1996), and some of them can meet the temperature stability requirements of UH type (-750±60ppm / ℃) dielectric materials.
[0059] When perovskite dielectric materials are sintered under a nitrogen-hydrogen reducing atmosphere, some boron sites in the perovskite crystal structure change from tetravalent to trivalent, forming oxygen vacancies in the crystal structure. 3+ Unstable; after absorbing a small amount of energy, it loses an electron and reverts to B. 4+ B 3+ Lost electrons are easily captured by oxygen vacancies in the crystal structure. These captured electrons are weakly bound electrons. Under the influence of an electric field, weakly bound electrons participate in electrical conduction, leading to semiconductorization, which in turn reduces insulation resistance and degrades reliability. This invention discovers that by adding the aforementioned auxiliary materials R1 to R4 and controlling their dosage, the reduction resistance of dielectric materials can be improved, the dielectric constant can be increased, the dielectric loss can be reduced, the temperature characteristics can be improved, and the reliability can be enhanced.
[0060] In this invention, the sintering temperature of the main material, strontium calcium zirconate titanate, is as high as 1350℃, which is higher than that of the inner electrode, Ni. This can easily cause MLCCs to crack or have other defects due to inconsistent shrinkage between the inner electrode and the dielectric material. This invention addresses this by adding the aforementioned proportions of sintering aids, which, together with R1-R4, lower the ceramic forming temperature of the dielectric material, resulting in a more suitable sintering temperature that is more conducive to matching the sintering of the inner electrode and achieving MLCC production.
[0061] The present invention also provides a method for preparing the reduction-resistant pulse energy storage ceramic dielectric material described in the above technical solution, comprising the following steps:
[0062] Strontium calcium zirconate titanate, auxiliary materials and sintering aids are mixed and sintered in a reducing atmosphere to obtain the reducing-resistant pulse energy storage ceramic dielectric material.
[0063] The auxiliary materials include R1, R2, R3 and R4;
[0064] R1 comprises an oxide or carbonate of at least one element of Mn, Cr, Co and Fe;
[0065] R2 comprises an oxide or carbonate of at least one element of Ba, Mg, Zr, Ca, Sr and Ti;
[0066] R3 comprises an oxide of at least one element of Ho, Y, Er, Dy and Sm;
[0067] R4 comprises an oxide of at least one element of Mo and V.
[0068] The application mixes strontium calcium titanate zirconate, auxiliary materials and sintering aids, and then sintering in a reducing atmosphere to obtain the anti-reduction type pulse energy storage ceramic dielectric material.
[0069] As an embodiment, the mixing method of strontium calcium titanate zirconate, auxiliary materials and sintering aids is wet ball milling; the rotation speed of the wet ball milling is 250-350 rpm, and in a specific embodiment, the rotation speed is 300 rpm; the time is 4-8 h, and in a specific embodiment, the time is 6 h; the ball milling medium used in the wet ball milling is zirconia ball; the diameter of the zirconia ball is 3-10 mm, and in a specific embodiment, the zirconia ball includes graded zirconia balls with a diameter of 3 mm and a diameter of 5 mm, wherein the mass ratio of the zirconia ball with a diameter of 3 mm to the zirconia ball with a diameter of 5 mm is 1:2; the ball-to-material ratio during the wet ball milling is 5-10:1, and in a specific embodiment, the ball-to-material ratio is 7:1; the solvent used in the wet ball milling is water, and in a specific embodiment, the solvent is deionized water; the ratio of the total mass of the main material, the auxiliary material and the sintering aid to the weight of the solvent used in the wet ball milling is 1:2-5, and in a specific embodiment, the ratio is 1:3; after the wet ball milling, the mixture liquid after the wet ball milling is dried; the drying temperature is 120-150℃, and in a specific embodiment, the temperature is 125℃; the time is 10-15 h, and in a specific embodiment, the time is 12 h; the particle size of the powder obtained after the wet ball milling is 120-250 nm, and in a specific embodiment, the particle size is 150-200 nm.
[0070] As an embodiment, after mixing strontium calcium titanate zirconate, auxiliary materials and sintering aids, the obtained mixture is sequentially granulated and formed, and the obtained green body is then sintered.
[0071] As an implementation form, the granulation is glue granulation; the glue added in the glue granulation process is polyvinyl butyral (PVB); the mass of the glue is 0.5-2% of the total mass of the main material, the auxiliary material and the sintering aid, and in a specific embodiment, is 1%; the glue is used in the form of a glue-alcohol solution; the concentration of the glue in the glue-alcohol solution is 10 wt%; the glue granulation is followed by sieving; the mesh size of the sieve used for the sieving is 40-100 mesh, and in a specific embodiment, is 60 mesh.
[0072] As an implementation form, the forming is press forming; the pressure of the press forming is 3-10 MPa, and in a specific embodiment, is 5 MPa; the pressure holding time is 30 s-2 min, and in a specific embodiment, is 1 min. The present application does not have special limitations on the shape and size of the green body obtained by the press forming, and the selection can be made according to the needs. In the embodiment of the present application, the green body obtained by the press forming is a circular tablet-shaped green body with a diameter of 10 mm.
[0073] As an implementation form, after the forming, the process further includes: degassing the green body obtained by the forming; the equipment used for the degassing is a degassing furnace; the temperature of the degassing is 400-500℃, and in a specific embodiment, is 450℃; the holding time is 3-5 h, and in a specific embodiment, is 4 h. The present application discharges the organic matter in the green body through degassing.
[0074] As an implementation form, the reducing atmosphere is a nitrogen-hydrogen atmosphere; the nitrogen-hydrogen atmosphere includes nitrogen and hydrogen; the volume ratio of the nitrogen and hydrogen is 100:3-10, and in a specific embodiment, is 100:5; the sintering includes: after the first sintering, cooling to perform the second sintering; the temperature of the first sintering is 1250-1280℃, and in a specific embodiment, is 1250℃; the holding time is 2-3 h, and in a specific embodiment, is 2 h; the temperature of the second sintering is 990-1010℃, and in a specific embodiment, is 1010℃; the holding time is 3-5 h, and in a specific embodiment, is 4 h; after the sintering, the process further includes: furnace cooling to room temperature.
[0075] The present application also provides an application of the anti-reduction pulse energy storage ceramic dielectric material in a capacitor.
[0076] The present application also provides a capacitor including a ceramic substrate and a metal electrode covering the surface of the ceramic substrate; the ceramic substrate is the anti-reduction pulse energy storage ceramic dielectric material or the anti-reduction pulse energy storage ceramic dielectric material prepared by the preparation method.
[0077] As an implementation form, the material of the metal electrode is copper or nickel; the thickness of the metal electrode is 0.01-0.03 mm, and in particular embodiments, is 0.02 mm.
[0078] As an implementation form, the preparation method of the capacitor is as follows: after surface treatment of a ceramic substrate, a conductive paste is coated on the surface of the ceramic substrate, and after drying, sintering is performed to obtain the capacitor; the surface treatment is polishing to remove surface impurities; the conductive paste is a copper electrode paste or a nickel electrode paste purchased on the market; the coating method is screen printing, and in particular embodiments, is screen printing; the drying temperature is 250-320°C, and in particular embodiments, is 280°C, and the time is 2-5 min, and in particular embodiments, is 3 min; the sintering temperature is 600-800°C, and in particular embodiments, is 700°C, and the holding time is 0.5-2 h, and in particular embodiments, is 1 h.
[0079] The technical solutions in the application will be described below in conjunction with the embodiments in the application, but they should not be understood as limitations to the protection scope of the application.
[0080] Embodiments 1-16
[0081] SrCO3, CaCO3, ZrO2, and TiO2 powders with a purity of 99.9% and a particle size of 50-180 nm are weighed according to the molar proportions in Table 1, and are mixed by wet ball milling for 6 h with deionized water as a solvent; the rotation speed of the wet ball milling is 300 rpm; the ball milling medium used is graded zirconia balls with a diameter of 3 mm, a diameter of 10 mm, and a diameter of 15 mm (mass ratio ); the ball-to-material ratio is 30:1; the total mass of the SrCO3, CaCO3, ZrO2, and TiO2 powders to the weight of the deionized water during the wet ball milling process is 1:2.5; the particle size of the obtained powder is 50-80 nm; then the powder is dried at 125°C for 11 h, calcined at 1160°C for 2 h in an air atmosphere, and then wet ball milled for 6 h for ball milling dispersion; the rotation speed of the wet ball milling is 250 rpm; the ball milling medium used is graded zirconia balls with a diameter of 3 mm and a diameter of 5 mm (mass ratio ); the ball-to-material ratio is 7:1; the material-to-water ratio is 1:2.5; the particle size of the obtained powder is 200-250 nm; finally, the powder is dried at 125°C for 11 h to obtain a main material represented by [(Ca x Sr 1-x )O] m [(Ti y Zr 1-y )O2] ; x, y, and m in the general formula are listed in Table 1.
[0082] The main material and the auxiliary material and the sintering aid (see Table 1 for the types and proportions of each raw material) are weighed according to the weight ratio, placed in a ball mill tank, wet ball milled for 6h with deionized water as the solvent, the rotation speed of the wet ball mill is 300rpm, the ball mill medium used is graded zirconia ball with a diameter of 3mm and a diameter of 5mm (mass ratio ), the ball-to-material ratio is 7:1, the ratio of the total mass of the main material, auxiliary material and sintering aid to the mass of deionized water during the wet ball milling process is 1:3, the particle size of the obtained powder is 150-200nm, then the obtained mixture is dried at 125℃ for 12h, after adding 10wt% polyvinyl butyral (PVB)-alcohol solution (the mass of PVB is 1% of the total mass of the main material, auxiliary material and sintering aid) to the obtained mixture, the mixture is ground and granulated using a maroon mortar, then the obtained granules are sieved through a 60 mesh sieve, the obtained granules are pressed into green compacts in the shape of a circle with a diameter of 10mm, the pressing pressure is 5MPa, the holding time is 1min, then the green compacts are heat treated in a degassing furnace at a temperature of 450℃ for 4h to remove the organic matter.
[0083] The degassed green compacts are sintered in a nitrogen-hydrogen atmosphere (the volume ratio of nitrogen to hydrogen is 100:5) furnace, first at 1250℃ for 2h, then cooled to 1010℃ for 4h, and then cooled to room temperature in the furnace, to obtain the anti-reduction type pulse energy storage ceramic dielectric material, i.e. the ceramic disc.
[0084] Table 1: Related formulations of Examples 1-16
[0085]
[0086]
[0087] Performance test
[0088] (1) The surface of the ceramic disc prepared in Examples 1-16 is polished to remove surface impurities, then electrode paste is coated, dried at 280℃ for 3min, and then sintered at 700℃ for 1h to form an electrode, then a disc capacitor is prepared, and the capacity value, dielectric loss, insulation resistance and temperature characteristics are tested, and the relative dielectric constant, insulation resistivity and capacity temperature coefficient are calculated, and the performance parameters are shown in Table 2.
[0089] Table 2: Related performance of the ceramic discs prepared in Examples 1-16
[0090]
[0091] From Table 2, it can be seen that the optimal group is the anti-reduction type pulse energy storage ceramic dielectric material prepared in Example 13, by adjusting the main material [(Ca x Sr 1-x )O] m [(Ti yZr 1-y )O2] ratio and the content of the auxiliary material, in a temperature range of 1250-1280℃, a dielectric constant of 100 and above, a dielectric loss of less than 0.02%, a volume temperature coefficient of between (-1000-1000) ppm / ℃, and 25℃ and 125℃ insulation resistivity of 10 13 Ω·cm above, the overall performance is high dielectric constant, low dielectric loss, high insulation resistance, excellent temperature characteristics, in the temperature range of-55-125℃, has a better temperature stability, meets the temperature stability requirements of UK type (-750±250ppm / ℃) dielectric material specified in the national standard (GB / T5596-1996), and part of the products meet the UH type (-750±60ppm / ℃) requirements.
[0092] (2) Figure 1 The SEM diagram of the main material calcium strontium zirconate titanate prepared in Example 13 shows that the particle size of the calcium strontium zirconate titanate powder is 200-250 nm, and the particles are uniform.
[0093] (3) Figure 2 The XRD diagram of the calcium strontium zirconate titanate prepared in Example 13 shows that the position and relative intensity of each diffraction peak are consistent with the standard PDF card (JCPDS NO. 35-0790) of calcium zirconate, indicating that the synthesis product has a single perovskite structure and good crystallinity, which facilitates to ensure that the material has good electrical properties.
[0094] (4) Figure 3 The cross-sectional SEM diagram of the ceramic wafer prepared in Example 13 shows that at this temperature, the ceramic is sintered dense inside, has few pores, and has no obvious defects.
[0095] (5) Figure 4 The surface SEM diagram of the ceramic wafer prepared in Example 13 shows that at this temperature, the ceramic wafer surface is dense, and the grain grows to 1 μm.
[0096] In summary, the anti-reduction type pulse energy storage ceramic dielectric material provided by the present application has a smaller dielectric loss on the basis of meeting the temperature characteristics of UH, and can meet the production needs of the highest end type of capacitor products.
[0097] Although the above examples have made a detailed description of the present application, it is only a part of the embodiments of the present application but not all the embodiments, and other embodiments can be obtained under the premise of no creativity according to the present embodiments, which all belong to the protection scope of the present application.
Claims
1. A reducing pulse-resistant energy storage ceramic dielectric material, characterized in that, The raw materials for preparation include calcium strontium zirconate titanate, auxiliary materials, and sintering aids; The chemical formula of the strontium calcium zirconate titanate is [(Ca x Sr 1-x )O] m [(Ti y Zr 1-y )O2], 0.43≤x≤1, 0.45≤y≤0.53, 0.85≤m≤1.30; The auxiliary materials include R1, R2, R3 and R4; R1 includes an oxide or carbonate of at least one of Mn, Cr, Co and Fe; The R2 includes an oxide or carbonate of at least one of Ba, Mg, Zr, Ca, Sr and Ti; The R3 includes an oxide of at least one element selected from Ho, Y, Er, Dy, and Sm; The R4 comprises an oxide of at least one of the elements Mo and V.
2. The reducing pulse-resistant energy storage ceramic dielectric material according to claim 1, characterized in that, The mass ratio of R1 to calcium strontium zirconate titanate is 0.01–0.2:100; the mass ratio of R2 to calcium strontium zirconate titanate is 0.2–1.2:100; the mass ratio of R3 to calcium strontium zirconate titanate is 0.3–1.3:100; and the mass ratio of R4 to calcium strontium zirconate titanate is 0.01–0.06:
100.
3. The reducing pulse-resistant energy storage ceramic dielectric material according to claim 1, characterized in that, The sintering aid includes SiO2 and / or B2O3; the mass ratio of the sintering aid to calcium strontium zirconate titanate is 0.1 to 0.4:
100.
4. The reducing pulse-resistant energy storage ceramic dielectric material according to claim 1, characterized in that, The preparation method of the strontium calcium zirconate titanate includes the following steps: mixing the raw materials corresponding to each element in the strontium calcium zirconate titanate according to the stoichiometric ratio and then calcining them to obtain strontium calcium zirconate titanate.
5. The reducing pulse-resistant energy storage ceramic dielectric material according to claim 4, characterized in that, The calcination temperature is 1100–1200℃, and the holding time is 1–3 hours.
6. The method for preparing the reducing pulse energy storage ceramic dielectric material according to any one of claims 1 to 5, characterized in that, Includes the following steps: Strontium calcium zirconate titanate, auxiliary materials and sintering aids are mixed and sintered in a reducing atmosphere to obtain the reducing-resistant pulse energy storage ceramic dielectric material. The auxiliary materials include R1, R2, R3 and R4; R1 includes an oxide or carbonate of at least one of Mn, Cr, Co and Fe; The R2 includes an oxide or carbonate of at least one of Ba, Mg, Zr, Ca, Sr and Ti; The R3 includes an oxide of at least one element selected from Ho, Y, Er, Dy, and Sm; The R4 comprises an oxide of at least one of the elements Mo and V.
7. The preparation method according to claim 6, characterized in that, The method of mixing strontium calcium zirconate titanate with auxiliary materials or mixing strontium calcium zirconate titanate, auxiliary materials and sintering aids is wet ball milling; the rotation speed of the wet ball milling is 250-350 rpm and the time is 4-8 h.
8. The preparation method according to claim 6, characterized in that, The sintering process includes: a first sintering followed by a cooling process for a second sintering; the temperature of the first sintering is 1250–1280°C, and the holding time is 2–3 hours; the temperature of the second sintering is 990–1010°C, and the holding time is 3–5 hours.
9. The application of the anti-reducing pulse energy storage ceramic dielectric material according to any one of claims 1 to 5 or the anti-reducing pulse energy storage ceramic dielectric material prepared by the preparation method according to any one of claims 6 to 8 in a capacitor.
10. A capacitor comprising a ceramic substrate and metal electrodes coated on the surface of the ceramic substrate, characterized in that, The ceramic substrate is the reducing pulse energy storage ceramic medium material according to any one of claims 1 to 5 or the reducing pulse energy storage ceramic medium material prepared by the preparation method according to any one of claims 6 to 8.